KIR3DS1-Mediated Recognition of HLA-*B51: Modulation of KIR3DS1 Responsiveness by Self HLA-B Allotypes and Effect on NK Cell Licensing - Carlomagno, Simona; Falco, Michela; Bono, Maria; Alicata, Claudia; Garbarino, Lucia; Mazzocco, Michela; Moretta, Lorenzo; Moretta, Alessandro; Sivori, Simona (Frontiers in Immunology, 2017)
Several studies described an association between KIR/HLA gene combinations and clinical outcomes in various diseases. In particular, an important combined role for KIR3DS1 and HLA-B Bw4-I80 in controlling viral infections as well as a higher protection against leukemic relapses in donor equipped with activating KIRs in haplo-HSCT have been described. Here we show that KIR3DS1 mediates positive signals upon recognition of HLA-B*51 (Bw4-I80) surface molecules on target cells, and that this activation occurs only in Bw4-I80neg individuals, including those carrying particular KIR/HLA combination settings. In addition, killing of HLA-B*51 transfected target cells mediated by KIR3DS1+/NKG2A+ NK cell clones from Bw4-I80neg donors could be partially inhibited by antibody-mediated masking of KIR3DS1. Interestingly, KIR3DS1-mediated recognition of HLA-B*51 could be better appreciated under experimental conditions in which the function of NKG2D was reduced by mAb-mediated blocking. This experimental approach may mimic the compromised function of NKG2D occurring in certain viral infections. We also show that, in KIR3DS1+/NKG2A+ NK cell clones derived from a HLA-B Bw4-T80 donor carrying 2 KIR3DS1 gene copy numbers, the positive signal generated by the engagement of KIR3DS1 by HLA-B*51 resulted in a more efficient killing of HLA-B*51 transfected target cells. Moreover, in these clones, a direct correlation between KIR3DS1 and NKG2D surface density was detected while the expression of NKp46 was inversely correlated with that of KIR3DS1. Finally, we analyzed KIR3DS1+/NKG2A+ NK cell clones from a HLA-B Bw4neg donor carrying cytoplasmic KIR3DL1. Although these clones expressed lower levels of surface KIR3DS1, they displayed responses comparable to those of NK cell clones derived from HLA-B Bw4neg donors and expressing surface KIR3DL1. Altogether these data suggest that, in particular KIR/HLA combinations, KIR3DS1 may play a role in the process of human NK cell education.